ABA enhanced cold tolerance of wheat 'dn1' via increasing ROS scavenging system. (2nd August 2020) - Yu, Jing; Cang, Jing; Lu, Qiuwei; Fan, Bo; Xu, Qinghua; Li, Weina; Wang, Xiutian
ABSTRACT: Abscisic acid (ABA) is an important plant hormone that plays significant roles in cold tolerance regulation. However, whether ABAimproves cold tolerance by increasing the activities of antioxidant enzymes in wheat remains unknown. In this study, the activities of antioxidant enzymes of the winter wheat variety 'dongnongdongmai 1ʹ (' dn1ʹ )afterthe application of exogenous ABA under low temperature (0°C, −10°C, −20°C, and −25°C) were investigated. Results showed that cold stress significantly increased H2 O2 and relative conductivity, whileABA significantly reduced this effect. ABA enhanced cold tolerance in both leaves and rhizomes at −10°C and −20 °Cby increasing CAT, SOD, POD, APX, GR, DHAR, and MDHAR. However, this tolerance was weakenedat −25°C with decreasing ASA, GSH, APX, DHAR, and MDHARthan at-10°C and −20°C.POD, GR, and DHARlevels peaked at −10°C, while CAT, SOD, GSH, APX, and MDHAR content in rhizomes peaked at −20°C. The rate of returning green was significantly increased after ABA treatment than in controls (93.5% vs 83.6 %). In ' dn1ʹ, rhizomes had a higher cold tolerance than leaves. Thereby, exogenous ABA could enhance cold tolerance byincreasing the activities of antioxidant enzymes.